2019
DOI: 10.1016/j.ijrobp.2018.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Impact of MRI Distortions: A Study on Head and Neck Cancers

Abstract: The dosimetric impact of distortions on 21 head and neck cancer magnetic resonanceeonly radiation therapy treatment plans was studied. Distorted computed tomography (CT) images were obtained by deforming patient CT scans with displacement fields from residual system and patientinduced susceptibility effects. The feasibility of magnetic resonanceeonly radiation therapy was demonstrated by a dose difference of less than 2% within the target volume for all dosimetric parameters evaluated between distorted CT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…The geometric inaccuracy of the target will potentially decrease the tumor control probability or overlap regions with the adjacent healthy structures, which could be detrimental for patients in terms of normal tissue complications. The proposed method reduced the geometric displacements to <2 mm, and studies showed that a 2‐mm error could cause ≤5% dosimetry uncertainty, which might be considered acceptable for the delivery of the absorbed dose . In this work, pelvis images were acquired from a medium‐size male.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The geometric inaccuracy of the target will potentially decrease the tumor control probability or overlap regions with the adjacent healthy structures, which could be detrimental for patients in terms of normal tissue complications. The proposed method reduced the geometric displacements to <2 mm, and studies showed that a 2‐mm error could cause ≤5% dosimetry uncertainty, which might be considered acceptable for the delivery of the absorbed dose . In this work, pelvis images were acquired from a medium‐size male.…”
Section: Discussionmentioning
confidence: 99%
“…Although images showed that most of the anatomy of the pelvis was inside of the 30‐cm DSV, the accuracy improvement outside of the 30‐cm DSV was particularly important for the dosimetry implementation where the body contour had to be geometrically accurate. Moreover, for some large patients, a large FOV was required to acquire images in anatomic regions, which could be outside of the 30‐cm DSV . Distortions on treatment plans and beam arrangements would also introduce dosimetry errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations